Age-dependent seroprevalence of SARS-CoV-2 antibodies in school-aged children from areas with low and high community transmission. - Lise Boey; Mathieu Roelants; Joanna Merckx; Hens, Niel; I Desombere; Els Duysburgh; Vandermeulen, Corinne (Eur J Pediatr, 2021)
It is not yet clear to what extent SARS-CoV-2 infection rates in children reflect community transmission, nor whether infection rates differ between primary schoolchildren and young teenagers. A cross-sectional serosurvey compared the SARS-CoV2 attack-rate in a sample of 362 children recruited from September 21 to October 6, 2020, in primary (ages 6-12) or lower secondary school (ages 12-15) in a municipality with low community transmission (Pelt) to a municipality with high community transmission (Alken) in Belgium. Children were equally distributed over grades and regions. Blood samples were tested for the presence of antibodies to SARS-CoV-2 with an enzyme-linked immunosorbent assay. We found anti-SARS-CoV-2 antibodies in 4.4% of children in the low transmission region and in 14.4% of children in the high transmission region. None of the primary schoolchildren were seropositive in the low transmission region, whereas the seroprevalence among primary and secondary schoolchildren did not differ significantly in the high transmission region. None of the seropositive children suffered from severe disease. Children who were in contact with a confirmed case (RR 2.9; 95%CI 1.6-4.5), who participated in extracurricular activities (RR 5.6; 95%CI 1.2-25.3), or whose caregiver is a healthcare worker who had contact with COVID-19 patients (RR 2.2; 95%CI 1.0-4.6) were at higher risk of seropositivity. If SARS-CoV2 circulation in the community is high, this will be reflected in the pediatric population with similar infection rates in children aged 6-12 years and 12-15 years. What is Known: •Children are generally less affected by COVID-19 than adults but SARS-CoV2 infection rates among children are not well known. •There were large regional differences in infection rates during the first wave of the SARS-CoV2 pandemic. What is New: •None of the primary schoolchildren (6-12 years) were seropositive for SARS-CoV2 in an area with a low community transmission, but infection rates were higher in adolescents (12-15 years). •In an area with high community transmission, seroprevalence rates in younger children were more comparable to those in adolescents.